2017
DOI: 10.1097/mib.0000000000001086
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of miR-21 and miR-126 in Mucosal Tissue from Patients with Inflammatory Bowel Disease

Abstract: This study shows that miR-126 levels are increased in UC and expressed in endothelial cells. miR-21 is expressed in subsets of monocytes/macrophages and T cells and may work as a potential biomarker to distinguish UC from CD. Quantitative in situ hybridization may be a powerful tool for such analysis as it combines overall expression with validation of cellular origin. Studies in larger cohorts may confirm this for clinical diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 36 publications
2
36
0
1
Order By: Relevance
“…For instance, miR-126 suppresses the inflammation in human gingival fibroblasts by downregulating inflammatory cytokines via targeting TRAF6 [30,31]. In our study, we found miR-126 to be negatively correlated with hs-CRP in CAD patients, negatively correlated with the levels of TNF-α and IL-6, and positively associated with the level of IL-10 in patients with CAD, and the underlying mechanism to explain the correlations have previously been demonstrated.…”
Section: Discussionsupporting
confidence: 60%
“…For instance, miR-126 suppresses the inflammation in human gingival fibroblasts by downregulating inflammatory cytokines via targeting TRAF6 [30,31]. In our study, we found miR-126 to be negatively correlated with hs-CRP in CAD patients, negatively correlated with the levels of TNF-α and IL-6, and positively associated with the level of IL-10 in patients with CAD, and the underlying mechanism to explain the correlations have previously been demonstrated.…”
Section: Discussionsupporting
confidence: 60%
“…MicroRNA levels vary under pathological conditions (Ha, ; Heneghan, Miller, Lowery, Sweeney, & Kerin, ; Ouellet, Perron, Gobeil, Plante, & Provost, ) and they can resist degradation in biological fluids which has opened the way for new fields of research looking for microRNAs as biomarkers for cancer (Heneghan et al., ; Park et al., ; Simpson, Lim, Moritz, & Mathivanan, ; Thorlacius‐Ussing, Schnack Nielsen, Andersen, Holmstrom, & Pedersen, ; Tie, Liu, Fu, & Zheng, ), inflammatory diseases like Crohn's disease and ulcerative colitis (Chapman & Pekow, ; Coskun, Bjerrum, Seidelin, & Nielsen, ), systemic lupus erythematosus (Heegaard, Carlsen, Skovgaard, & Heegaard, ), or sepsis (Dumache et al., ) among many other conditions including development and aging, metabolic syndromes, and infections (Ghai & Wang, ).…”
Section: Circulating Micrornas: the Paradigm Shiftmentioning
confidence: 99%
“…Accumulating studies disclose that dysregulation of miRNAs including miR‐31, miR‐155, and miR‐26b is involved in the pathological processes of a variety of immune diseases including psoriasis . MiR‐126, located on human chromosome 9q34.3, has been reported to participate in the development and progression of multiple immune diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and inflammatory bowel disease (IBD) . However, to the best of our knowledge, the role of miR‐126 in the etiology of psoriasis has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] MiR-126, located on human chromosome 9q34.3, has been reported to participate in the development and progression of multiple immune diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and inflammatory bowel disease (IBD). [16][17][18] However, to the best of our knowledge, the role of miR-126 in the etiology of psoriasis has not been reported. Therefore, this study aimed to investigate the miR-126 expression of lesional skin and its correlation with clinical features in psoriasis patients and to explore the effect of upregulation of miR-126 on cells' proliferation, apoptosis, and inflammation in human keratinocytes.…”
Section: Introductionmentioning
confidence: 99%